ANALYSIS OF FEASIBILITY OF TOMATO (Solanum lycorpercium) FARMING IN AIKMEL DISTRICT, EAST LOMBOK REGENCY - Eno Rihatul Fitri; Muhammad Anwar (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2021)
The total production of tomatoes in Aikmel District, East Lombok Regency in 2019 was 46.853 Kw and a land area of ​​204 Ha. While in 2015-2017 experienced fluctuations with an average annual production of 33,610 Kw. The aim of this study were: 1) To determine the level of costs and income of tomato farming, 2) To determine the feasibility level of tomato farming and 3) To find out the constraints faced by farmers in tomato farming. This research used descriptive method, the data collection technique used survey technique, the number of respondent farmers was determined by Quota Sampling as many as 30 people. The types of data used were qualitative data and quantitative data. The results showed that the land area of ​​the respondent farmers in Aikmel District was mostly between 0.10 – 0.15 Ha, which was an average of 8 people (27%). With the average amount of costs incurred in tomato farming in Aikmel District, namely Rp. 6.611.309/LLG or Rp. 220,377/Ha. Meanwhile, the average income earned was Rp. 3,435,357/LLG or Rp. 114,512/Ha. Based on the calculation of the R/C ratio in tomato farming of 1.4, showed that tomato farming was feasible in Aikmel District. The obstacles faced by farmers in tomato farming in Aikmel District were: lack of capital, the presence of pests and diseases and the lack of transportation costs. Keywords: farming, tomato, income